Pemanfaatan Limbah Ternak Sebagai Pupuk Organik Untuk Kemandirian Pertanian Berkelanjutan Desa Karanggedang Kecamatan Sidareja - Latifah, Anisatul; Maghfirotun, Siti Wahyu; Mu'alimah, Mu'alimah; Masamah, Siti; Amaludin, Slamet; Nazah, Lutfi Alifatun; Rizqiana, Lisda; Ma’rifan, Annas; Azzahra, Amira Shofiana; Soleman, Ibnu; Jannah, Ade Ul Jannah (Jaanur ElBarik Indonesia, 2025)
This community service activity aims to provide education on the use of livestock waste as organic fertilizer for independent sustainable agriculture in Karanggedang village, Sidareja sub-district. The implementation method is socialization, education, and practice. The results of the activity show an increase in knowledge and skills, which is indicated by the ability of participants to answer questions correctly and the emergence of a strong desire to produce fertilizer independently. Thus, this training is expected to be able to support the implementation of sustainable agriculture in Karanggedang Village.